2014
DOI: 10.14742/ajet.585
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence the perceived advantages and relevance of Facebook as a learning tool: An extension of the UTAUT

Abstract: <span style="font-family: Times New Roman; font-size: small;"> </span><p>Social media technologies are becoming a fundamental component of education. This study extends the Unified Theory of Acceptance and Use of Technology (UTAUT) to identify factors that influence the perceived advantages and relevance of Facebook as a learning tool. The proposed model is based on previous models of UTAUT. Constructs from previous models were used such as performance expectancy, effort expectancy, social in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 69 publications
6
54
0
2
Order By: Relevance
“…These results concur with numerous studies that reported the main reasons for individuals to use social media are to socialise, communicate, and maintain relationships (Escobar-Rodríguez, Carvajal-Trujillo, & Monge-Lozano, 2014;Everson, Gundlach, & Miller, 2013;Robyler et al, 2010). The current student generation belong to the millennial generation (i.e.…”
Section: Malaysian Perspectivesupporting
confidence: 92%
“…These results concur with numerous studies that reported the main reasons for individuals to use social media are to socialise, communicate, and maintain relationships (Escobar-Rodríguez, Carvajal-Trujillo, & Monge-Lozano, 2014;Everson, Gundlach, & Miller, 2013;Robyler et al, 2010). The current student generation belong to the millennial generation (i.e.…”
Section: Malaysian Perspectivesupporting
confidence: 92%
“…Same results were revealed when we came to test H4, were the results showed that students costumed to technology more likely to have a positive intention to use e-learning system. In fact, the effect of both hedonic motivation and habit revealed very significant impact on students behavioural intention to use Facebook as a learning as reported by Escobar-Rodríguez et al (2014).…”
Section: Discussionmentioning
confidence: 73%
“…Last, [19] employed UTAUT2 to discover the perceived advantages and relevance of Facebook as a learning tool. Analysis of data from a questionnaire completed by business administration students at a Spanish public university (N=956) showed that Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Hedonic Motivation and Habit all influenced students' intention to use Facebook in relation to their studies.…”
Section: Utaut and Social Media Adoptionmentioning
confidence: 99%